Formulation and Evaluation of Bi-Layer Tablet of Nebivolol and Nateglinide - Jangid, Vikash; Chatterjee, Arindam; Pandey, Saurabh; Agarwal, Vikash; Sharma, Deeksha (Journal of Biomedical and Pharmaceutical Research, 2023)
In the present work, the Bilayered matrix type tablet were prepared by direct and wet granulation technique, in which immediate release layer ( by direct compression) contains Nebivolol and extended release layer (by wet granulation) contains Nateglinide. All the developed bilayer tablets were evaluated for weight variation, friability, thickness and hardness. The percent deviation from the average weight, friability, thickness and hardness was found to be within the prescribed official limits. Release profile of Nebivolol from formulations indicate that lower MCC (Formulations CF1 and CF3) and lactose (Formulation CF3) content displayed higher release rates as compared to formulation with higher MCC and lactose content (Formulation CF2). Also the concentration of KYRON T-314 is also found to influence the release rate of the drug. It was found that formulation containing the highest concentration of superdisintegrants (Formulation CF3) has grater release then other subsequent formulations (Formulations CF1 and CF3). Similarly, the release profile of Nateglinide from formulations indicate that lower HPMC K15M (Formulation CF3) and lactose (Formulation CF3) content displayed higher release rates as compared to formulation with individual HPMC K15M, HPMC K100M, EC (Formulations CF1 and CF2) and higher lactose content (Formulations CF1 and CF2).